Isolation and characterization of mono terpenoid From roots of syzygiumsamarangense - M. MADHAVI; M. RAGHU RAM (International Journal of Pharma and Bio Sciences, 2017)
This study reports the isolation and characterization of a new terpenoid extracted from the aqueous extract of Syzygium samarangense roots. The plant is proved as a potential source for phytochemicals for traditional use as therapeutics. Traditionally the roots are used as diuretic and are given to alleviate edema. These are also used for treatment of itching. Aqueous extracts of the root has been subjected to chromatographic techniques to isolate the Terpenoid compounds. Their structures were analyzed by using spectroscopic methods including ultraviolet (UV), electron ionization mass spectrometry (MS), hydrogen nuclear magnetic resonance (HNM R) and CNM R the final bioactive compound was identified as (1E)-2-methylbuta-1,3-dien-1-yl 8a-methyl-5-(methylamino) decahydronaphthalene-2-carboxylate. The preliminary bioactivity of the compound was also evaluated. The method of isolation is simple, cost effective and efficient.